Metode Pembinaan Akhlak Anak Usia Sekolah Dasar Oleh Orangtua Pada Masa New Normal Di Jorong Gaduang Kecamatan Pantai Cermin Kabupaten Solok - Mutiara, Delfita; Iswantir, Iswantir (ANTHOR: Education and Learning Journal, 2022)
This research is motivated by that at this time in Jorong Gaduang when children are in the process of education at home or in the new normal period of education. Moral development at home indicates that there are methods from some parents in Jorong Gaduang in fostering themorals of children who are lacking. The less optimal method of moral development given bythe parents is that parents do not provide good examples at home. In addition, parents also donot pay attention to or supervise the use of gadgets and the association of children's peers.Then there are also parents who do not give advice and punishment to children when theymake mistakes. This type of research is a field research, with a qualitative descriptive approach. From the research that has been done, it can be concluded that parents have fostered the morals of elementary school-age children with various methods, namely the exemplary method, the habituation method, the advice method, the punishment method and the attention method. In addition to applying these 5 methods during the new normal, parents also apply the gift-giving method and the story method in fostering children's morals. Even though parents have implemented the moral development method as optimally as possible, in this new normal period there are still elementary school-aged (SD) children who behave badly because there are several obstacles parents have in fostering morals during the new normal period, namely: a) parental responsibilities to children while studying at home is less, namely the limited time. b) Parents have difficulty controlling the use of online media, namely the use of gadgets. c) Difficulties of parents in controlling their child's association with peers, causing children to play more than study, worship and help parents.